Scanning electron microscopy analysis of the growth of dental plaque on the surfaces of removable orthodontic aligners after the use of different cleaning methods - Levrini L; Novara F; Margherini S; Tenconi C; Raspanti M (Dove Medical Press, 2015)
Luca Levrini, Francesca Novara, Silvia Margherini, Camilla Tenconi, Mario Raspanti Department of Surgical and Morphological Sciences, Dental Hygiene School, Research Centre Cranio Facial Disease and Medicine, University of Insubria, Varese, Italy Background: Advances in orthodontics are leading to the use of minimally invasive technologies, such as transparent removable aligners, and are able to meet high demands in terms of performance and esthetics. However, the most correct method of cleaning these appliances, in order to minimize the effects of microbial colonization, remains to be determined. Purpose: The aim of the present study was to identify the most effective method of cleaning removable orthodontic aligners, analyzing the growth of dental plaque as observed under scanning electron microscopy. Methods: Twelve subjects were selected for the study. All were free from caries and periodontal disease and were candidates for orthodontic therapy with invisible orthodontic aligners. The trial had a duration of 6 weeks, divided into three 2-week stages, during which three sets of aligners were used. In each stage, the subjects were asked to use a different method of cleaning their aligners: 1) running water (control condition); 2) effervescent tablets containing sodium carbonate and sulfate crystals followed by brushing with a toothbrush; and 3) brushing alone (with a toothbrush and toothpaste). At the end of each 2-week stage, the surfaces of the aligners were analyzed under scanning electron microscopy. Results: The best results were obtained with brushing combined with the use of sodium carbonate and sulfate crystals; brushing alone gave slightly inferior results. Conclusion: On the basis of previous literature results relating to devices in resin, studies evaluating the reliability of domestic ultrasonic baths for domestic use should be encouraged. At present, pending the availability of experimental evidence, it can be suggested that dental hygienists should strongly advise patients wearing orthodontic aligners to clean them using a combination of brushing and commercially available tablets for cleaning oral appliances. Keywords: scanning electron microscopy, orthodontic appliances, oral hygiene, biofilm, clear aligners